2020
DOI: 10.1002/ange.201914571
|View full text |Cite
|
Sign up to set email alerts
|

Stable Mesoionic N‐Heterocyclic Olefins (mNHOs)

Abstract: We report a new class of stable mesoionic N‐heterocyclic olefins, featuring a highly polarized (strongly ylidic) double bond. The ground‐state structure cannot be described through an uncharged mesomeric Lewis‐structure, thereby structurally distinguishing them from traditional N‐heterocyclic olefins (NHOs). mNHOs can easily be obtained through deprotonation of the corresponding methylated N,N′‐diaryl‐1,2,3‐triazolium and N,N′‐diaryl‐imidazolium salts, respectively. In their reactivity, they represent strong σ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 77 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This classification arises from the fact that while following octet rules, no resonance structures can be drawn for MICs without charge separation, unlike their well-established N-heterocyclic carbene (NHC) counterparts [5,[7][8][9]. Therefore, not surprisingly, the synthetic scope of MICs has expanded rapidly, opening up the possibility of introducing additional donor substituents, such as pyridine, to generate bidentate ligands [10][11][12][13][14][15][16] or post-modifications to N-heterocyclic olefins (NHOs) [17,18] and mesoionic imines (MIIs) [19,20], which are promising candidates for small molecule activation [5]. Suntrup et al showed in 2017 that the insertion of a pyridyl moiety into 1,2,3-triazoleand 1,4-triazolylidene-based Re(I) carbonyl complexes drastically improves the overall π acceptor character of the ligand, while the incorporation of an MIC unit results in a greater σ donor strength compared to the well-established bpy ligand [21].…”
Section: Introductionmentioning
confidence: 99%
“…This classification arises from the fact that while following octet rules, no resonance structures can be drawn for MICs without charge separation, unlike their well-established N-heterocyclic carbene (NHC) counterparts [5,[7][8][9]. Therefore, not surprisingly, the synthetic scope of MICs has expanded rapidly, opening up the possibility of introducing additional donor substituents, such as pyridine, to generate bidentate ligands [10][11][12][13][14][15][16] or post-modifications to N-heterocyclic olefins (NHOs) [17,18] and mesoionic imines (MIIs) [19,20], which are promising candidates for small molecule activation [5]. Suntrup et al showed in 2017 that the insertion of a pyridyl moiety into 1,2,3-triazoleand 1,4-triazolylidene-based Re(I) carbonyl complexes drastically improves the overall π acceptor character of the ligand, while the incorporation of an MIC unit results in a greater σ donor strength compared to the well-established bpy ligand [21].…”
Section: Introductionmentioning
confidence: 99%
“…This classification arises from the fact that while following octet rules, no resonance structures can be drawn for MICs without charge separation, unlike their well-established Nheterocyclic carbenes (NHC) counterparts [5,[7][8][9]. Therefore, not surprisingly, the synthetic scope of MICs has expanded rapidly, opening up the possibility of introducing additional donor substituents, such as pyridine, to generate bidentate ligands [10][11][12][13][14][15][16] or post-modifications to N-heterocyclic olefins (NHO) [17,18] and mesoionic imines (MII), [19,20] which are promising candidates for small molecule activation [5]. Suntrup et al, in 2017 showed, that the insertion of a pyridyl moiety into 1,2,3-triazole-and 1,4triazolylidene-based Re(I) carbonyl complexes drastically improves the overall 𝜋 − acceptor Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%